Keepin' it Real in Central Europe: The DIY Rap Music Careers of Male Hip Hop Artists in Austria. (June 2018) - Reitsamer, Rosa; Prokop, Rainer
This article sets out to broaden our understanding of the significance of authenticity, locality and language for the development of a do-it-yourself (DIY) rap music career by taking male rap artists in Austria as an example. Drawing on interviews carried out in 2014–2015 with two groups of rap artists from different social and cultural backgrounds who embarked on their rap music careers in the early 1990s and the early 2000s, we analyse their rap lyrics and the social and economic contexts in which these individuals became rappers. We examine how the artists articulate claims to authenticity by appropriating African-American rap styles, meanings and idioms and blending them with local languages and references to local cultures and national politics. We also examine the rappers' relationship to the music industry and the use of informal channels for the production, performance and consumption of rap and hip hop in general. The article suggests that the DIY careers of these rap artists depend on both the rappers' use of music to articulate claims to authenticity and their ability to form (trans-)local networks for sharing skills, knowledge and other resources, as well as on Austria's cultural policy and the changes in the music industry that have taken place in recent years.